How Do Wii Know: Anecdotal Records Go Digital. (23rd August 2013) - Bates, C.C.
Abstract: Anecdotal records have long been used as a means of formative assessment. This article explores how traditional anecdotal records can be enhanced with digital technology. Using a portable device and one of many available note‐taking applications, teachers have the opportunity to create a richer picture of the student. Highlighted in this Teaching Tip is information on how to take digital notes, how to organize them to assist in making instructional decisions, and ways to use the app's embedded media options to document student learning.